Marketing Strategies For SMEs in The Culinary Sector: a Case Study of Queen Cake in Makassar - Mutiara; Marhawati Najib; Sumiati Tahir (Economics and Business Journal (ECBIS), 2026)
MSMEs must have a strong marketing plan in order to compete with their rivals due to technological improvements and growing business competitiveness. An efficient marketing plan is necessary to guarantee company expansion and optimize earnings. This study aims to determine the appropriate marketing strategy to increase the sales turnover of Queen Cake products. This research is a descriptive study using a qualitative approach. Respondents in this study were the owner of the Queen Cake business and four employees, two from the production department and two from the marketing department. Data collection procedures used in the study included observation, interviews, and documentation. The data obtained were analyzed using a SWOT analysis. The results showed that the strategy implemented by the Queen Cake business was in quadrant one, namely SO (Strengths-Opportunities), using an aggressive strategy. The Queen Cake shop business focuses on strategies using all its strengths and exploiting opportunities to create synergistic conditions and great potential for achieving growth and success.